تأثير تدريبات بأسلوب البلايومترك داخل الماء وعلى اليابسة في تطوير بعض انواع القوة الخاصة والإنجاز بالوثب الطويل للمتقدمين - علي, أحمد بهاء الدين (Sulaimani Journal for Humanities, 2025)
The study aims to acknowledge the impact of plyometric training performed on land and in water on the development of some aspects of pro jumpers’ muscle strength and long jump achievement. The study therefore assumed the probability of some variations related to the appearance of statistically significant resulted between the pre and post tests applied on the first and second experimental groups regarding the development of some aspects of pro jumpers’ muscle strength and long jump achievement. In terms of methodology, the study relied on experimental method since this type of methodology is matching the research’s nature. Thus, experimental method could be counted as the best method to achieve the set objectives. The sample of the study consisted of 8 pro long jumpers belonging to Peshmarga Athlete Club. After identifying the variations and the testing methods, the training program for the training season 2017 was applied. Following the performance of processing the results statistically, the researcher concluded statistical significance in terms of spirituality collected from the explosive legs power testing, ultimate legs power testing, and strength characteristic by speed testing for the distance of accomplishment board between the pre and post tests applied on the first and second experimental groups. The researcher is delighted to offer some suggestions regarding the performance of plyometric training performed on land on the ground that it is has a tremendous positive impact in developing the special agilities for the long jumpers. Finally, the researcher highlights the necessity of conducting similar studies taking into account other physical abilities in other sport fields.